IGBT device health monitoring - design of data logging and analysis - Venkatachalapathy Bragathishwaran (2016)
Insulated Gate Bipolar Transistors (IGBT) are widely used in Power Electronic Converters and industrial applications e.g. motor drives and grid connected inverter. When Power converters are employed in safety critical applications, the reliability of converters is highly critical. To improve the reliability of the system, health of each component must be assured. For a power converter the IGBTs are reported to have high failure rate. Hence it is important to develop methods to access the health and predict the remaining useful lifetime of the device. The failures of IGBTs are mainly due to number of stress factors when the device is under operation. The objective of this project is to implement the monitoring circuit, converting it into a proper ADC signal, using modelling or algorithm acquisting the monitored signal in the Texas instrument F28335 Digital signal processor. In particular, this project aims to develop hardware test rig for AD converter and data logging system.